Microsoft Research Treelet Translation System: IWSLT Evaluation - Menezes, Arul; Quirk, Chris (Proceedings of the International Workshop on Spoken Language Translation, 2005)
The Microsoft Research translation system is a syntactically informed phrasal SMT system that uses a phrase translation model based on dependency treelets and a global reordering model based on the source dependency tree. These models are combined with several other knowledge sources in a log-linear manner. The weights of the individual components in the log-linear model are set by an automatic parameter-tuning method. We give a brief overview of the components of the system and discuss its performance at IWSLT in two tracks: Japanese to English (supplied data and tools), and English to Chinese (supplied data and tools).